Social Environment Factors, Diet Quality, and Body Weight in 12-Year-Old Children from Four Public Schools in Puerto Rico - Serrano, Mónica; Torres, Roxana; Pérez, Cynthia M.; Palacios, Cristina (Puerto Rico Health Sciences Journal, 2014)
Objective: To explore the association of social-environment (SE) factors and diet quality (DQ) with weight status in a group of children in Puerto Rico (PR). Methods: A cross-sectional study in a sample of 114 12-year-old children enrolled in 4 public schools in the San Juan Metropolitan area in Puerto Rico (PR) during the 2012-2013 school year. These children completed a self-administered questionnaire on socio-demographic characteristics and SE, with information on family meal patterns; parental feeding styles; parental, peer, and school support for healthy eating; physical activity (PA); and frequency of PA and sedentary times. The participants also completed at 24-hour dietary recall interview to determine DQ. This was assessed with the Healthy Eating Index (HIE)-2010, an instrument that evaluates compliance with the Dietary Guidelines for Americans. Body mass index (BMI) was calculated and categorized as healthy weight, overweight, or obese. Results: 36% of participants were overweight/obese. In terms of DQ, 55% had “poor” DQ, 45% had diets that “need improvement”, and none had “good” DQ. Children of healthy weight (75.0%) reported more frequent family meals than did overweight/obese children (57.5%; p = 0.05). No other significant associations were found between SE factors and DQ or body weight status. Conclusion: Most of the participants were of healthy weight but had poor quality diets. Having a healthy weight was positively associated with frequent family meals.